2023
DOI: 10.3390/su15097332
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intellectual Capital on Service Firm Financial Performance in Emerging Countries: The Case of Vietnam

Abstract: This paper evaluates the effect of intellectual capital (IC) on firm financial performance in the service sector in an emerging country, Vietnam. This research is dissimilar from earlier ones for the following reasons: (i) this is the first study of IC’s impact on service firms at different knowledge intensity levels, sizes, and ownerships in an emerging country, Vietnam; (ii) it expresses empirical evidence in details of service activities, particularly the research and development, financial, and technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The dynamic panel model (Nguyen 2023), using the one-year-lagged dependent variable as the regressor, was estimated using system GMM (generalized method of moments), as implemented by the pdynmc package in the R statistical environment (Fritsch et al 2019). The estimation uses the two-step model with time dummy variables.…”
Section: Panel Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamic panel model (Nguyen 2023), using the one-year-lagged dependent variable as the regressor, was estimated using system GMM (generalized method of moments), as implemented by the pdynmc package in the R statistical environment (Fritsch et al 2019). The estimation uses the two-step model with time dummy variables.…”
Section: Panel Estimationmentioning
confidence: 99%
“…Structural capital is a conglomerate of infrastructure elements such as intellectual property, internal processes and procedures, information systems, research and development investments, and, more generally, knowledge-related assets (Moon and Kym 2006;Nguyen 2023). A readily available approximation is the size of intangible assets, excluding goodwill.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Costa et al (2020) determined the impact of ICs on Portuguese tourism firm performance (ROA). Recently, Nguyen (2023) recently reported that there exists a substantial correlation between IC efficiency and the performance of Vietnamese firms, with human capital efficiency exhibiting the most pronounced positive influence on performance. Sohel Rana and Hossain (2023) discovered a significant and positive correlation between IC efficacy and the performance of listed non-financial companies in Bangladesh.…”
Section: Intellectual Capital and Firm Performancementioning
confidence: 99%
“…A company can create added value and improve its performance when a firm can use its intellectual capital and physical capital simultaneously. Capital employed can also assist companies in developing good internal and external relationships with employees, consumers, suppliers, creditors, and governments (Nguyen, 2023).…”
Section: Capital Employed Efficiencymentioning
confidence: 99%